Morphological and Physiological Framework Underlying Plant Longevity in Arabidopsis thaliana - Wang, Yukun; Kumaishi, Kie; Suzuki, Takamasa; Ichihashi, Yasunori; Yamaguchi, Nobutoshi; Shirakawa, Makoto; Ito, Toshiro (Frontiers in Plant Science, 2020)
Monocarpic plants have a single reproductive phase, in which their longevity is developmentally programmed by molecular networks. In the reproductive phase of Arabidopsis thaliana, the inflorescence meristem (IM) maintains a central pool of stem cells and produces a limited number of flower primordia, which results in seed formation and the death of the whole plant. In this study, we observed morphological changes in the IM at cellular and intracellular resolutions until the end of the plant life cycle. We observed four biological events during the periods from 1 week after bolting (WAB) till the death of stem cells: 1) the gradual reduction in the size of the IM, 2) the dynamic vacuolation of IM cells, 3) the loss of the expression of the stem cell determinant WUSCHEL (WUS), and 4) the upregulation of the programmed cell death marker BIFUNCTIONAL NUCLEASE1 (BFN1) in association with the death of stem cells. These results indicate that the stem cell population gradually decreases in IM during plant aging and eventually is fully terminated. We further show that the expression of WUS became undetectable in IM at 3 WAB prior to the loss of CLAVATA3 (CLV3) expression at 5 WAB; CLV3 is a negative regulator of WUS. Moreover, clv3 plants showed delayed loss of WUS and lived six weeks longer compared with wild-type plants. These results indicated that the prolonged expression of CLV3 at 4-5 WAB may be a safeguard that inhibits the reactivation of WUS and promotes plant death. Finally, through transcriptome analysis, we determined that reactive oxygen species (ROS) are involved in the control of plant longevity. Our work presents a morphological and physiological framework for the regulation of plant longevity in Arabidopsis.